Static electric dipole polarizabilities of atoms and molecules : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Chemistry at Massey University, Albany, New Zealand - Lim, Ivan S. (Massey University, 2004)
The static dipole polarizabilities and ionization potentials of the first and second main group elements, including the charged ions, are obtained from all-electron relativistic coupled-cluster theory using a scalar relativistic Douglas-Kroll Hamiltonian. Spin-orbit coupling effects are investigated using a fully relativistic four-component Dirac-Coulomb-Hartree-Fock scheme followed by a second-order many-body perturbation treatment to account for electron correlation. Periodic trends in the dipole polarizabilities and the ionization potentials are discussed. In each case, a detailed discussion on electron correlation and relativistic effects are given. A relationship for relativistic and electron correlation effects between the dipole polarizability and the ionization potential is established. Particular attention is paid to the evaluation of a near basis set limit quality of the dipole polarizabilities. This is accomplished by the evaluation of all-electron basis sets used, followed by an extensive study on the convergence behavior of the dipole polarizabilities with respect to a finite basis set expansion. The present all-electron dipole polarizabilities are believed to be very precise, especially for charged ions where the availability of experimental values are limited. Scalar relativistic small-core pseudopotentials are fitted and their performance is tested in terms of static dipole polarizabilities and ionization potentials. It is demonstrated that the small core definition of the pseudopotential (nine-valence electron for the main group 1 and ten-valence electron for the main group 2 elements) enables us to safely omit core-valence correlation without scarifying accuracy. Following atomic dipole polarizabilities, applications are made to molecules starting with alkali dimers and their singly charged ions. The scalar relativistic pseudopotentials of this study are used to calculate equilibrium bond lengths, dissociation energies, vibrational frequencies and the dipole polarizabilities of these dimers. The change in the molecular dipole polarizabilities from the corresponding atomic dipole polarizabilities are discussed in terms of molecular bonding models. Simple ammonia complexes of the alkali-metals and their singly charged ions are studied. The equilibrium geometries, dissociation energies, harmonic vibrational frequencies as well as the dipole polarizabilities of these complexes are given.
Keywords: Polarization (Electricity); Dipole moments; Atoms; Molecules; Fields of Research::250000 Chemical Sciences::250100 Physical Chemistry (Incl. Structural)::250107 Electrochemistry